Nocturnal phenotypical features of obstructive sleep apnea (OSA) in asthmatic children1. Issue 6 (30th November 2012) - Gutierrez, Maria J.; Zhu, Junjia; Rodriguez‐Martinez, Carlos E.; Nino, Cesar L.; Nino, Gustavo
Abstract Background Asthma and obstructive sleep apnea (OSA) often coexists during childhood. To delineate this clinical association, we investigated the phenotypical features of OSA in asthmatic children. Specifically, we hypothesized that asthmatic children have a distinct OSA phenotype that involves a higher prevalence of Rapid‐Eye‐Movement (REM)‐related breathing abnormalities relative to children with OSA alone. Methods We conducted a retrospective cross‐sectional analysis of 141 children aged 2–12 years with OSA diagnosed by polysomnography (PSG) in our sleep center. Outcomes included PSG parameters, maximal %SaO2 REM desaturations and prevalence of REM‐related OSA. Multivariate linear regression model or logistic regression model was built to study the joint effect of asthma and OSA parameters with control for potential confounders (significance level P < 0.05). Results Baseline respiratory parameters, obstructive apnea–hypopnea index (OAHI) severity, and oxygenation during NREM sleep were unaffected by the presence of asthma in children with OSA. In contrast, maximal %SaO2 REM desaturation, REM–OAHI and prevalence of REM‐related OSA in children with moderate–severe OSA were significantly increased in asthmatic children with OSA compared to subjects with OSA alone. Multivariate analysis revealed that the association between asthma and REM‐related OSA parameters is independent of asthma control, BMI, age, and gender. The presence of REM‐related OSA in asthmatics was unaffected by rhinitis or atopic status. Conclusion These results demonstrate that asthma is associated with REM‐related breathing abnormalities in children with moderate–severe OSA. The link between asthma and REM‐related OSA is independent of asthma control and obesity. Further research is needed to delineate the REM‐sleep biological mechanisms that modulate the phenotypical expression of OSA in asthmatic children. Pediatr Pulmonol. 2013; 48:592–600. © 2012 Wiley Periodicals, Inc.